Património Mundial e os sítios culturais em risco iminente. Primeiras reflexões - Costa, Inês de Carvalho (CEM – Cultura, Espaço & Memória, 2021)
Considering the rising impact of heritage matters in the international community and assuming the growth of worldwide recognized sites, it is relevant to reflect about their hierarchies and effectiveness of protection. Therefore, starting from the analysis of UNESCO’s List of World Heritage in Danger (2018-2019), it is proposed to clarify the degree of preservation, recognition and communication of these sites through the study of UNESCO’s webpage and some fundamental texts for the issue. Ultimately, cultural sites in imminent danger will be addressed, through the analyses of main threats and their consequences for the safeguarding and preservation of the properties.